The estimated effect of graphic warning labels on smoker's intention to quit in Shanghai, China: a cross-sectional study - Ruiping Wang; Yan Qiang; Yan Zhu; Xiangjin Gao; Qiong Yang; Bin Li (BMC, 2021)
Abstract Background Tobacco consumption is the leading cause of death worldwide. Overwhelming studies demonstrate graphic warning labels (GWLs) on cigarette packs are effective in eliciting negative response to tobacco smoking, modifying beliefs about tobacco dangers, and increasing reported intention to quit, but the estimated effect of GWLs on smoking cessation intention among smokers is still limited in China. In this study, we aim to understand the smoking intensity, smoking duration and smoking cessation intention among current smokers, and to explore how their smoking cessation intention would be influenced by the GWLs in Shanghai. Methods From January to June 2021, we totally recruited 1104 current smokers in Songjiang district and Fengxian district of Shanghai by multistage sampling design. We used Android pad assisted electronic questionnaire for data collection, and then implemented logistic regression for odds ratio (OR) and 95% confidence interval (CI) calculation to explore how smoking cessation intention would be influenced by the GWLs among current smokers. Results One thousand one hundred four current smokers included 914 males (82.79%), with an average age of 43.61 years. 58.06% of current smokers reported smoking cessation intention due to GWLs. Logistic regression indicated a higher percentage of smoking cessation intention due to GWLs was among female smokers [OR = 2.41, 95% CI (1.61-3.59)], smokers with smoking intensity < 20 cigarette/day [OR = 1.92, 95% CI (1.44-2.55)], smokers with tobacco burden < 20% [OR = 1.94, 95% CI (1.35-2.79)], and among smokers had plan to quit in a year [OR = 6.58, 95% CI (4.71-9.18). Smokers with higher individual monthly income had lower percentage of smoking cessation intention (OR were 0.35, 0.46 and 0.41). Meanwhile, among 642 current smokers without plan to quit in a year, approximately 40% of them reported smoking cessation intention due to GWLs. Conclusions Smoking cessation intention due to the assumed GWLs on cigarette packs is high among current smokers in Shanghai, especially in female smokers, smokers with light tobacco burden and mild nicotine dependence. Incorporating smoking intensity as well as smoking burden into the implementation of GWLs as tobacco control measures would discourage smoking in China.